Clonality pattern assessed by ERIC-PCR and REP-PCR in extended-spectrum beta- lactamase-producing Escherichia coli and Klebsiella pneumoniae isolates from patients with nosocomial urinary tract infections. Hospital Regional Lambayeque, Peru - López-Ramírez, Kelly Lelia (2018)
Objective: To determine the clonality pattern assessed by ERIC-PCR and REP-PCR in extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae isolates from patients with urinary tract infections at the Hospital Regional Lambayeque (HRL) from July to November 2015. Materials and methods: A total of 30 ESBL-producing E. coli and K. pneumoniae clinical isolates collected from the HRL’s emergency, medicine, surgery and pediatrics services were assessed. The clonal relationship was determined using the ERIC-PCR and REP-PCR markers. For clusters, UPGMA algorithm with Bio Rad Quantity One 1-D analysis software was used, thus generating dendrograms through the union of the electrophoretic profiles obtained by both molecular markers. Results: From the molecular analysis, three predominant clonal patterns were found in E. coli and two in K. pneumoniae. Conclusions: The study reveals the clonal dissemination of potentially pathogenic microorganisms in the emergency service, where it is urgent to implement measures for their prevention and control.